Examining Effective Teaching Practices in Higher Education - Toni M Paoletta MEd (Adult Education Research Conference, 2019)
Contingent faculty represent the largest instructional group in higher education today yet few receive any andragogic training prior to teaching. Does this impact their effectiveness in the classroom?
Keywords: teacher effectiveness; faculty preparedness; andragogy